Chlorella mirabilis as a Potential Species for Biomass Production in Low-Temperature Environment - Shukla, Satya P.; Kviderova, Jana; Tříska, Jan; Elster, Josef (Frontiers in Microbiology, 2013)
Successful adaptation/acclimatization to low temperatures in micro-algae is usually connected with production of specific biotechnologically important compounds. In this study, we evaluated the growth characteristics in a micro-scale mass cultivation of the Antarctic soil green alga Chlorella mirabilis under different nitrogen and carbon sources followed by analyses of fatty acid contents. The micro-scale mass cultivation was performed in stable (in-door) and variable (out-door) conditions during winter and/or early spring in the Czech Republic. In the in-door cultivation, the treatments for nitrogen and carbon sources determination included pure Z medium (control, Z), Z medium + 5% glycerol (ZG), Z medium + 5% glycerol + 50 µM KNO3 (ZGN), Z medium + 5% glycerol + 200µM NH4Cl (ZGA), Z medium + 5% glycerol + 1 mM Na2CO3 (ZNC), Z medium + 5% glycerol + 1 mM Na2CO3 + 200µM NH4Cl (ZGCA) and Z medium + 5% glycerol + 1 mM Na2CO3 + 50 µM KNO3 (ZGCN) and were performed at 15°C with an irradiance of 75 µmol m-2 s-1. During the out-door experiments, the night-day temperature ranged from -6.6°C to 17.5°C (daily average 3.1±5.3 °C) and irradiance ranged from 0 to 2300 µmol m-2 s-1 (daily average 1500±1090 µmol m-2 s-1). Only the Z, ZG, ZGN and ZGC treatments were used in the out-door cultivation. In the in-door mass cultivation, all nitrogen and carbon sources additions increased the growth rate with the exception of ZGA. When individual sources were considered, only the effect of 5% glycerol addition was significant. On the other hand, the growth rate decreased in the ZG and ZGN treatments in the out-door experiment, probably due to carbon limitation. Fatty acid composition showed increased production of linoleic acid in the glycerol treatments. The studied strain of C. mirabilis is proposed to be a promising source of linoleic acid in low temperature mass cultivation biotechnology. This strain is a perspective model organism for biotechnology in low-temperature conditions.